Managing HR in SMES: An Empirical case study of an Indian firm - Jain, Isha (2012)
Small and Medium enterprises play a significant role in a nation's development. One of the most often neglected managerial aspect found in SMEs is the Human Resource Management. This report discusses the indigenous practices of SMEs that inhibit the formalisation of human resource development. The second section of this report critically analyses the HR practices of a small firm in India and proposes steps for formalisation of its HR strategy.